Hybrid fibre breeze block: a sustainable and lightweight innovation for modern construction - Anuar, Izzat; Ismail, Sallehan; Saleh, Ani Maslina (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Hybrid Fibre Breeze Block is an innovative product intended to transform semi-structural wall applications by integrating the complementary advantages of polypropylene (PP) and nylon fibres. This lightweight solution overcomes the shortcomings of traditional lightweight concrete, providing improved compressive strength, decreased porosity, and greater durability. The Hybrid Fibre Breeze Block is designed to fulfil the increasing need for ecological, economical, and high-performance building materials, marking a notable progression in contemporary construction technology. This product is experimented with for up to 56 days by incorporating hybrid fibres into lightweight foamed concrete (LFC), enhancing the material's microstructure and performance. The blocks demonstrate enhanced fracture resistance, superior load distribution, and heightened moisture resistance due to sophisticated material engineering. This invention offers significant benefits, including decreased structural weight, minimal material use, and improved thermal and fire resistance. These characteristics enable energy-efficient and environmentally sustainable construction methods that minimize carbon footprints while adhering to green building standards. The Hybrid Fiber Breeze Block, with its scalable manufacturing capabilities, presents significant commercialization opportunities in the construction industry, especially for sustainable housing and infrastructure projects. This product facilitates socio-economic development by lowering building expenses while simultaneously advancing environmental sustainability, in accordance with global green construction trends.